2005
DOI: 10.1088/0953-4075/38/6/l02
|View full text |Cite
|
Sign up to set email alerts
|

H(2p) excitation by 54.4 eV electrons

Abstract: In response to the recent measurements of the 54.4 eV e–H(2p) reduced Stokes parameters by Gradziel and O'Neill (2004 J. Phys. B: At. Mol. Opt. Phys. 37 1893) we perform corresponding calculations using two recently developed techniques. These are the propagating exterior complex scaling direct approach to the solution of the underlying Schrödinger equation, and the box-based convergent close-coupling method. We find the results to be almost identical to the Laguerre-based convergent close-coupling method of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…All the PECS calculations presented in this tutorial, and other publications emanating from this research [33][34][35][36][37][38][39][40][41][42][43], are in excellent agreement with other state-of-the-art computational methods and measurements, where available. We consider that the PECS method now offers complete solutions for e-H collisions in four important respects.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…All the PECS calculations presented in this tutorial, and other publications emanating from this research [33][34][35][36][37][38][39][40][41][42][43], are in excellent agreement with other state-of-the-art computational methods and measurements, where available. We consider that the PECS method now offers complete solutions for e-H collisions in four important respects.…”
Section: Resultssupporting
confidence: 66%
“…PECS reduced Stokes parametersP 1 ,P 2 andP 3 and related parameters P l , γ and P + for e-H 1s-2p scattering at E 0 = 54.4 eV. CCC box-based calculations (CCC-B) [40] and measurements of Yalim et al [65], Gradziel and O'Neill [64] and Williams and Mikosza [66] are also shown.…”
Section: Ground-state Hydrogen Scatteringmentioning
confidence: 77%
See 2 more Smart Citations
“…The reduced Stokes parameters, P 1 , P 2 and P 3 for the H(2p) state at an incident electron energy of 54 eV. Closed squares, Yalim, Cvejanovic and Crowe (1997); closed and open circles, Williams and Mikosza (2006); closed triangles, Gradziel and O'Neill (2004); open triangles, O'Neill et al (1998);open squares, Nic Chormaic, Chwirot and Slevin (1993); open diamonds, Williams (1986); full line, the PECS theory of Bartlett et al (2005). Adapted from Williams and Mikosza (2006 More detailed reviews of angular and polarization correlation and superelastic scattering studies were given by Andersen, Gallagher and Hertel (1988) Andersen et al (1997), and Andersen and Bartschat (2001).…”
Section: Angular and Polarization Correlationsmentioning
confidence: 99%